Application of a predictive model of axillary lymph node status in patients with sentinel node metastasis from breast cancer. A retrospective cohort study. (November 2016) - Vieni, Salvatore; Graceffa, Giuseppa; La Mendola, Roberta; Latteri, Stefania; Cordova, Adriana; Latteri, Mario Adelfio; Cipolla, Calogero
Abstract: Background and objectives: The Axillary Lymph Node Dissection (ALND) is the standard treatment in patients with invasive breast cancer and sentinel node metastasis, but in 60% of the cases there is no further axillary neoplastic involvement, so this invasive intervention represents an overtreatment. The purpose of the study is to identify patients with low risk of additional nodal metastases, to omit ALND. Methods: The MSKCC Additional nodal metastasis nomogram was applied on a sample of 175 patients with invasive breast cancer who underwent ALND after detection of macrometastasis with the extemporaneous examination of the sentinel lymph node. Patients were classified as "low risk" when the result of the nomogram was ≤50%. Sensitivity, specificity, positive and negative predictive values and AUC (Area Under Curve) of the ROC curve of the nomogram were then calculated. Results: A cut-off by 50% yielded 92.3% sensitivity, 81, 4% specificity, 80% positive predictive value and 92.9% negative predictive value. The ROC curve AUC in these patients was 0.885. Conclusions: The MSKCC nomogram has proven to be an effective tool in estimating the axillary lymph node status and it can potentially be used to better select the patients with sentinel node macrometastasis who can actually benefit from ALND. Highlights: In about 60% of patients with metatstic SLN, there is no further axillary neoplastic involvement. MSKCC nomogram is a valid tool available to select the patients for axillary lymphadenectomy. The nomogram has a high reliability and a remarkable utility in clinical practice.